Coxiella burnetii infects osteoclasts and alters their differentiation and function in a type IV secretion system-dependent manner - Lai, Chaobo; Siddique, Md Nur A Alam; Asghar, Faiza; Su, Xudong; Schulze-Luehrmann, Jan; Jia, Yewei; Escarrega, Edith Alexandar; Bachmann, Elke; Bozec, Aline; Lang, Roland; Lührmann, Anja; Soulat, Didier (Frontiers in Immunology, 2026)
Chronic Q fever is caused by persistent infection with the Gram-negative bacterium Coxiella burnetii. The mechanisms underlying this persistence remain elusive, but the presence of the bacteria in the bone marrow of C. burnetii-infected patients has been demonstrated. Therefore, we investigated the potential role of osteoclasts, the bone-resorbing cells, in harboring C. burnetii during infection. The histological analysis of bones from a murine model of Q fever revealed the presence of C. burnetii inside osteoclasts. In vitro infection assays confirmed that osteoclasts can be infected with C. burnetii and supported bacterial replication in a type IVB secretion system (T4BSS)-dependent manner. Wild-type C. burnetii infection inhibited osteoclast differentiation and bone-resorbing activity, while the T4BSS mutant enhanced the differentiation and bone-degrading function of osteoclasts. Taken together, our findings identify osteoclasts as a potential host cell for C. burnetii. This opens new perspectives on the mechanisms that may underlie chronic Q fever as well as questioning the putative consequences on bone biology in chronically affected patients.